Pyramidal tract activation due to subthalamic deep brain stimulation in Parkinson's disease. Issue 8 (7th June 2017) - Mahlknecht, Philipp; Akram, Harith; Georgiev, Dejan; Tripoliti, Elina; Candelario, Joseph; Zacharia, Andre; Zrinzo, Ludvic; Hyam, Jonathan; Hariz, Marwan; Foltynie, Thomas; Rothwell, John C.; Limousin, Patricia
ABSTRACT: Background: Subthalamic deep brain stimulation (STN‐DBS) is an effective treatment for Parkinson's disease (PD), but can have side effects caused by stimulus spread to structures outside the target volume such as the pyramidal tract. Objectives: To assess the relevance of pyramidal tract activation with STN‐DBS in PD. Methods: In a multimodal, blinded study in 20 STN‐DBS patients, we measured stimulation thresholds for evoking electromyographic activity in orbicularis oris and first dorsal interosseous muscles at each of 150 electrode sites. We also modeled the electric field spread and calculated its overlap with the estimated anatomical location of corticospinal and corticobulbar tracts from primary motor cortex using 3 Tesla MRI probabilistic tractography. Results: Mean resting motor thresholds were significantly lower for the contralateral orbicularis oris (3.5 ± 1.0 mA) compared with ipsilaterally (4.1 ± 1.1 mA) and with the contralateral first dorsal interosseous (4.0 ± 1.2 mA). The modeled volumes of corticobulbar and corticospinal tract activated correlated inversely with the resting motor threshold of the contralateral orbicularis oris and first dorsal interosseous, respectively. Active motor thresholds were significantly lower compared with resting motor thresholds by around 30% to 35% and correlated with the clinically used stimulation amplitude. Backward multiple regression in 12 individuals with a "lateral‐type" speech showed that stimulation amplitude, levodopa equivalent dose reduction postsurgery, preoperative speech intelligibility, and first dorsal interosseous resting motor thresholds explained 79.9% of the variance in postoperative speech intelligibility. Conclusions: Direct pyramidal tract activation can occur at stimulation thresholds that are within the range used in clinical routine. This spread of current compromises increase in stimulation strengths and is related to the development of side effects such as speech disturbances with chronic stimulation. © 2017 International Parkinson and Movement Disorder Society